IMPLEMENTATION OF LEARNING THEORY IN PAI LEARNING AND ITS RELEVANCE TO CURRICULUM DEVELOPMENT - Mohamad Erihadiana; Taupik Hamdani; Risma Nurlela; Moch Ardia Putra; Bilal Zakawali Al-Fathoni (SOSIOEDUKASI, 2025)
Learning theory has an important role in the development of the Islamic Religious Education (PAI) curriculum, because it can provide a scientific basis for designing an effective learning experience. This research explores various learning theories, such as constructivism, behaviorism, and cognitivism, as well as their implications for PAI learning. This study uses a qualitative approach with the systematic literature review (SLR) method which examines various results of previous research related to the application of learning theory to PAI learning and its relevance to curriculum development. The analysis of the data needs of this SLR method is through steps, namely the identification step of the research focus and the screening  stage of various indexed journal articles using inclusion and exclusion criteria. The results of this study show that in general, cognitive theory emphasizes the cognitive structure of students. Thus, the subject matter delivered in PAI lessons can be adjusted to the ability of students, then in behaviorsime theory is seen as a process of behavior change as a result of the interaction between stimulus and response, this theory is very suitable for the development of children's behavior in order to strengthen the good habits that have been formed so that they do not disappear slowly,  while constructivistic learning, according to the author, is a learning process that involves a student who is required to learn actively, innovatively and have an independent and capable way of thinking in overcoming problems that the teacher gives based on their understanding and involves experience well.